ICHTHYOFAUNA OF THE MARIMBONDINHO RIVER, FURNAS RESERVOIR, MINAS GERAIS, BRAZIL - Nobile, André Batista; Azevedo-Santos, Valter Monteiro; Soares, Claudio Lopes; Manzano, Felipe Viana; Oliveira, Claudio [UNESP]; de Lima, Felipe Pontieri (Oecologia Australis, 2024)
Ichthyofauna surveys are essential for conservation efforts in reservoirs. Here we present a list of fish species found in the Marimbondinho River, a tributary of the Furnas HPP reservoir in Minas Gerais, Brazil. Fish captures were conducted using gillnets and cast nets at five sampling points during six campaigns in 2018 and 2019. We recorded a total of 1,892 individuals belonging to 31 species, distributed in 16 families and four orders. Four fish species were considered long-distance migrants, and five were identified as non-natives. None of the captured species are listed as threatened on the official Brazilian list. Order Characiformes exhibited the highest species richness; in which Anostomidae and Characidae were the families with great species richness. Hoplosternum littorale was the most abundant species, presented in approximately 22% of all the captures. Overall, the results indicate that the ichthyofauna of Marimbondinho River is similar to those typically observed in Brazilian reservoirs, with the expected richness and number of migratory species. We expect this study can help in future monitoring programs and, fundamentally, to propose conservation and management measures on endemic and migratory species of Furnas reservoir.
Keywords: anthropic impacts; fish ecology; ichthyofauna survey; Neotropical fishes